2009
DOI: 10.1523/jneurosci.2217-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Motor Output Is Altered by Spike-Timing-Dependent Changes in the Human Corticospinal Pathway

Abstract: Repeated pairs of timed presynaptic and postsynaptic potentials cause lasting changes in efficacy of transmission at many synapses. The corticospinal tract is the major pathway controlling voluntary movement in humans, and corticospinal neurons have monosynaptic connections to motoneurons of many muscles. We hypothesized that corticospinal transmission in humans could be altered by delivering, to the corticospinal-motoneuronal synapses, timed pairs of presynaptic volleys (produced by cortical stimulation) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
177
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(198 citation statements)
references
References 43 publications
20
177
1
Order By: Relevance
“…The center of the coil was initially placed over the inion with current flowing downwards in the center of the coil (Taylor and Gandevia 2004). The optimal location for corticospinal tract stimulation was assessed by moving the coil laterally and caudally (Martin et al 2009) and was marked on a tightly fitting cap. For all subjects, CMEPs were elicited in the right FDI with stimulation to the right of the inion.…”
Section: Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The center of the coil was initially placed over the inion with current flowing downwards in the center of the coil (Taylor and Gandevia 2004). The optimal location for corticospinal tract stimulation was assessed by moving the coil laterally and caudally (Martin et al 2009) and was marked on a tightly fitting cap. For all subjects, CMEPs were elicited in the right FDI with stimulation to the right of the inion.…”
Section: Stimulationmentioning
confidence: 99%
“…Investigations of the spinal stretch reflex after motor training have demonstrated changes involving the motoneuron pool, and these appear to be related to the acquisition of specific motor tasks (Carp and Wolpaw 1994;Meunier et al 2007;Nielsen et al 1993;Perez et al 2005;Sale 1988;Wolf et al 1995;Wolpaw et al 1994;Wolpaw and Lee 1989). In addition, motoneuronal responses to corticospinal input can be acutely changed after short and prolonged strong voluntary contractions (MVCs) (e.g., Gandevia et al 1999;Giesebrecht et al 2010Giesebrecht et al , 2011Petersen et al 2003), and conditioning of the corticospinal-motoneuronal synapse by paired stimulation can alter corticospinal transmission in a way that is consistent with spike-timing-dependent plasticity (Taylor and Martin 2009).…”
mentioning
confidence: 99%
“…3,4 In PAS, noninvasive transcranial magnetic stimulation (TMS) is synchronized with noninvasive peripheral nerve electrical stimulation (PNS); signals are timed to coincide at synapses at cortical 3 or the spinal cord [5][6][7] level to enhance corticospinal neuron excitability. A single PAS session applied to one nerve can induce transient (up to 90 min) 4 plasticity in healthy subjects; importantly, one work in healthy subjects has shown that the effect of the protocol repeated for 3 days lasts for at least 2 days after the last stimulation session.…”
Section: Introductionmentioning
confidence: 99%
“…SAS involves repeat pairing of peripheral nerve stimulation and TMS pulses over M1 cortex or the cervicomedullary junction to yield near simultaneous arrival of the two inputs at the alpha motor neuron pool in the spinal cord [1,[95][96][97]. The protocol delivers ~ 100 repeat pairings once every 10 seconds [1,95] or 360 pairs once every 5 seconds [96] requiring 15-20 minutes of supra threshold nerve stimuli and TMS pulses.…”
Section: Paired Associative Stimulation (Pas)mentioning
confidence: 99%
“…The protocol delivers ~ 100 repeat pairings once every 10 seconds [1,95] or 360 pairs once every 5 seconds [96] requiring 15-20 minutes of supra threshold nerve stimuli and TMS pulses. In controls, SAS targeting muscles of the lower limb facilitates spinal Hoffman reflexes [95][96][97] and their recruitment [95]. SAS targeting the FDI leads to increases in MEP amplitude that are attributed to changes in the corticospinal-motor neuron synapses and follows STDP principles [51].…”
Section: Paired Associative Stimulation (Pas)mentioning
confidence: 99%